Equilibrium Isotherms, Kinetics, and Thermodynamic Mechanisms of a Novel Polyacrylamide-Strychnos potatorum Seed-Derived Activated Carbon Composite for Aqueous Hardness Removal - Yohan L. N. Mathota Arachchige; T. D. Fernando (Journal of Chemistry)
Hardness in water is responsible for both residential and industrial problems. Moreover, drinking hard water is suspected as the main cause of chronic kidney disease of unknown etiology (CKDu) in Sri Lanka. The major constituents that are responsible for water hardness are calcium and magnesium ions. In this study, a composite was synthesized using activated carbon of Strychnos potatorum seeds (ACSP) and acrylamide to remove hardness in drinking water. The synthesized composite was characterized using Fourier transform infrared-attenuated total reflection (FTIR-ATR) spectroscopy and scanning electron microscope (SEM). According to this study, the process of removal of hardness depends on the contact time, adsorbent dosage, initial contents, and pH of the solution. The adsorption data were well fitted to the Freundlich isotherm and the pseudo-second-order kinetic models. Furthermore, environmental samples collected from Anuradhapura, Sri Lanka, which is well known for water with high hardness, were treated with an adsorbent, and hardness was reduced effectively. Moreover, the adsorption appeared to be spontaneous in nature. Finally, it can be concluded that this adsorbent can be used as an effective hardness-removing agent.